Infrastructure, market access, and agricultural prices: evidence from Madagascar - Minten, Bart (International Food Policy Research Institute, 1999)
The effect of recent agricultural market reforms in many developing countries is often measured through tests for market integration by analyzing co-variation of food prices. However, market integration studies often fail to link the discovery of the lack of integration to causal factors. This analysis documents and relates price variation to structural determinants in the case of Madagascar. The spatial variability between communities is linked to the distance to a paved road, the quality of the road, access to soft infrastructure, and the level of competition between traders. Differences in seasonal variation are mainly related to the differential opportunity costs of capital in rice villages and to hard infrastructure in non-rice villages. Communities that lack basic infrastructure show lower prices during the harvest season and higher seasonal gaps. Moreover, it is shown that road distance matters more than road quality during the harvest period as there is no strong relationship between road quality and the producer price decline per unit of time. While the presence of roads shows up in relatively higher producer prices, it does not automatically lead to more competition among traders. Hence, investment in hard infrastructure is not sufficient to successfully increase market access. However, soft infrastructure on top of hard infrastructure seems beneficial for increased producer prices, reduced price variability, and improved market integration.